Food safety and quality systems in developing countries. Volume one, - Gordon, André (Academic Press, 2015)
This book considers both the theoretical and practical aspects of food safety and quality systems implementation by major world markets and new and emerging markets in developing countries. This reference examines issues facing exporters and importers of traditional foods the characteristics of the food and its distribution channels, and market access from a historical and current context to present best practices. This must-have reference offers real-life, practical approaches for foods from around the world, offering help to those who have found it difficult to implement sustainable, certifiable food safety and quality systems into their businesses and provides scientifically sound solutions to support their implementation.
Keywords: Food -- Developing countries -- Safety measures.; Food -- Quality -- Developing countries.; Food industry and trade -- Developing countries.; Exports -- Developing countries.; elektronické knihy; electronic books